2010
DOI: 10.3899/jrheum.090687
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean Fever in Children Presenting with Attacks of Fever Alone

Abstract: FMF in young children may begin with attacks of fever alone, but it progresses to typical FMF disease over the next 2.9 +/- 2.2 years. Our study demonstrates that clinical heterogeneity at presentation is more likely to indicate a feature of a disease in development, rather than to mark distinct phenotypes of FMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 21 publications
4
36
1
4
Order By: Relevance
“…Familial Mediterranean fever (FMF) is a recessively inherited disease associated with a mutated anti-inflammatory protein, known as pyrin/marenostrin [1]. Non-Ashkenazi Jews, Turks, Arabs, and Armenians are more commonly affected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Familial Mediterranean fever (FMF) is a recessively inherited disease associated with a mutated anti-inflammatory protein, known as pyrin/marenostrin [1]. Non-Ashkenazi Jews, Turks, Arabs, and Armenians are more commonly affected.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, Erysipelas-like erythema may also appear. Although today, the molecular basis of the disease is better understood, and genetic testing is available, the diagnosis remained clinical [1,2]. Persistent inflammation in about 30 % of FMF patients may progress to amyloidosis, in some.…”
Section: Introductionmentioning
confidence: 99%
“…86,136,145 The attacks occur suddenly, with high-grade fever (38.5À40 C) and severe malaise. 151 Moderate to severe abdominal pain occurs in 95% of patients, and is secondary to an acute generalized peritonitis. 152 On physical examination patients often have abdominal distension and intense rebound pain, mimicking an acute abdomen, which leads to abdominal surgery (appendectomy or cholecystectomy) in 30À40% of FMF patients.…”
Section: Geneticsmentioning
confidence: 99%
“…Candi date criteria sug gested by some as mar kers of a severe disease-including early age of dis ease onset, high colchicine dose needed to prevent attacks, certain features of the attack (such as frequency), carriage of two (versus one only) MEFV mutations, homo zygosity for the Met694Val variant and experiencing typical arthritis episodes-could be tested in this setting. 7,8 Finally, any such consortium might encoun ter two expected difficulties in deter mining new severity scoring systems for paediatric FMF. First, Padeh et al 8,9 have shown that during the first 2 years of life (that is, very early age of onset) the dis ease pheno type is very mild and manifests with attacks of fever alone.…”
Section: News and Viewsmentioning
confidence: 99%